Legal Review Of The Responsibility Of Online Gambling Criminal Acts In Indonesia - Joko Christopher Samosir; Suci Ramadani; Ismaidar Ismaidar (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This study discusses the accountability of perpetrators of online gambling crimes in Indonesia from the perspective of applicable positive law. Online gambling is a form of cybercrime that has developed along with advances in information and communication technology, and has various negative impacts on society, including economic losses, moral damage, and increasing crime rates. The main focus of this study is to examine how legal regulations in Indonesia, especially in the Criminal Code (KUHP), the Electronic Information and Transactions Law (UU ITE), and other related regulations, regulate and ensnare online gambling perpetrators, both as the main perpetrators, platform providers, and service users. This study uses a normative juridical method with a statutory approach and a case approach. Data were obtained through literature studies and analysis of relevant court decisions. The results of the study show that although Indonesian positive law has regulated the prohibition of gambling, there are still gaps in norms and challenges in implementation, especially related to evidence, jurisdiction of cross-border perpetrators, and adaptation of law enforcement officers to digital modus operandi. The conclusion of this study emphasizes the need for synchronization of regulations and increased law enforcement capacity, including the formation of more comprehensive special regulations regarding online gambling crimes. This is important so that the criminal responsibility of the perpetrator can be enforced effectively within the framework of justice and legal certainty.